(3MGTjI eYGde GdOjfs - (3GdeGRfOQGfj, GdCUagGfj, MSGe GdOjf, eMeO UGdM Hf CMeO, J (B1081 (3g`s ((3Ydj Hf cQHdGFj SHMGfhQOjs)
(3ChdgG (B:s
(3fMeOc Gddge (B... (3Ef HYV CNdGFj Mjf QCi eG YdbJg Ydi eYGde GdOjf dDdD efThQ QGSdfj CMQQ dge ahGFOg hCfXQ dge aQGFOg hGeQ Ydjg eQhQG aCLHJ eSDhdge hGfLRJ eCehdge hLYdJg (B...s
(3BNQgG (B:s
... (3dG jbGd aj bUU GdbQBf OdGdI Ydi bOQI GdHTQ Ydi GdEYLGR MjK cGf cKjQG efgG CcKQ ef KdK BjGJ dMcjGI dbeGf hMcGjI eDef Bd aQYhf dGfG fbhd djSJ GdHdGZI hMSf GdJCdja aj GdeYfi (B.. (3bO hbY GdaQGZs
(3JHUQI GdYfhGf (B:s
(3aj eYQV GdMOjK Ydi MGTjI GdgRGQLQjHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B1 - 232( 1956)s
(3GdPQjYI (B6 - 58 (406)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs